Comparison of Disposcope endoscope with Macintosh laryngoscope for laryngoscopy - Ziyu Gu; Liang Zhu; Zhouquan Wu (Anesthesiology and Perioperative Science, 2023)
Abstract Purpose Disposcope is a novel fibreoptic intubation device that allows visualization of the glottis without aligning the oral, pharyngeal, and tracheal axes. This device may offer advantages in improving glottis exposure, or reducing hemodynamic disturbance, and minimizing movement of the upper cervical spine (C-spine). In this study, we aimed to evaluate laryngoscopy using Disposcope compared to Macintosh laryngoscope. Methods This study enrolled 60 adult patients (American Society of Anesthesiologists physical status 1 and 2), both male and female, underwent lumbar spine surgery, scheduled for general anesthesia with endotracheal intubation. We compared the Cormack and Lehane grade, hemodynamic response, and the maximal change in the angle between adjacent cervical vertebrae and cumulative upper C-spine movement between Disposcope and Macintosh laryngoscope. A crossover trial design was employed, with half of the patients being exposed to the glottis using the Macintosh laryngoscope first, followed by the Disposcope, and vice versa for the other half. Results The intubation time in the Disposcope group was significantly lower than that in the Macintosh laryngoscope group (P < 0.01). Using the Disposcope resulted in improved views of the glottis (Z = −4.82, P < 0.01). Cormack and Lehane grade I views were achieved with the Disposcope in more patients than the Macintosh laryngoscope (36.7% versus 13.3%, P < 0.01). Grade II views were obtained in 58.3% of patients with the Disposcope, whereas a lower percentage (43.3%) was observed with the Macintosh laryngoscope. The incidence of grade III views was significantly lower with the Disposcope than with the Macintosh laryngoscope (5% versus 33.3%, P < 0.01). Additionally, there was significantly less hemodynamic disturbance (mean arterial pressure and heart rate) with the Disposcope compared to the Macintosh laryngoscope (P < 0.01). Finally, the median cumulative upper C-spine movement was greater with the Macintosh laryngoscope than with the Disposcope (26.9° versus 9.4°, P < 0.01). Conclusions In comparison to the Macintosh laryngoscope, the Disposcope provided improved views of the glottis and resulted in less hemodynamic disturbance and movement of the upper C-spine during laryngoscopy in patients.